Mini-chromosome maintenance complexes form a filament to remodel DNA structure and topology - Slaymaker, Ian M. (Oxford University Press, 2013)
Deregulation of mini-chromosome maintenance (MCM) proteins is associated with genomic instability and cancer. MCM complexes are recruited to replication origins for genome duplication. Paradoxically, MCM proteins are in excess than the number of origins and are associated with chromatin regions away from the origins during G1 and S phases. Here, we report an unusually wide left-handed filament structure for an archaeal MCM, as determined by X-ray and electron microscopy. The crystal structure reveals that an α-helix bundle formed between two neighboring subunits plays a critical role in filament formation. The filament has a remarkably strong electro-positive surface spiraling along the inner filament channel for DNA binding. We show that this MCM filament binding to DNA causes dramatic DNA topology change. This newly identified function of MCM to change DNA topology may imply a wider functional role for MCM in DNA metabolisms beyond helicase function. Finally, using yeast genetics, we show that the inter-subunit interactions, important for MCM filament formation, play a role for cell growth and survival.